1997
DOI: 10.1007/bf02481777
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of woven metal fibre reinforced glass matrix composites

Abstract: Abstract. A processing route has been developed for the fabrication of metallic fibre mat reinforced glass matrix composites. For the model experiments reported here, a commercially available satin woven stainless steel 316L fibre mat was used as the reinforcement and soda-lime glass as the matrix. The process involves two steps: (1) the infiltration of the intra-and inter-tows regions of the fibre mats with silica sol using electrophoretic deposition and (2) the fabrication of a composite by cold uniaxiat pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In ref. [17], it is, e.g., found that tough metal fibers in a brittle glass matrix give a higher composite toughness when the adhesion is low. A similar observation about the level of adhesion will be made in this article.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [17], it is, e.g., found that tough metal fibers in a brittle glass matrix give a higher composite toughness when the adhesion is low. A similar observation about the level of adhesion will be made in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous work about this specific fibre material, the present study combines it with a matrix material to a fibre-matrix composite. Static, conventional applications of fibre-matrix composites have been proposed for composites of bioglass 20 , 21 or cordierite 22 , 23 . In the field of biomedical engineering, metallic 24 , 25 and since then also non-metallic 26 , 27 fibre networks have been tested for their ability to improve bone cement mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional wisdom would suggest that conductive fibers would best serve as the deposition electrode, i.e., the matrix particles deposit directly on the fibers. Carbon fibers, 5 carbon‐coated SiC fibers, 6–9 nickel‐coated carbon fibers, 10,11 stainless‐steel fibers, 12–15 and polyoyrrole‐coated fibers 17 have been used. Most experiments were conducted in an aqueous suspension under a constant voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been used to introduce matrices into fiber preforms, i.e., chemical vapor infiltration (CVI), 1 solution infiltration including sol–gel and polymer precursor approaches, 1 pressure filtration (PF), 2 vibration‐assisted infiltration, 3,4 and electrophoretic deposition (EPD) 5–15 . Both CVI and solution infiltration have low penetration efficiency and hence it is difficult to obtain a dense green body; it is also difficult by pressure filtration.…”
Section: Introductionmentioning
confidence: 99%